Marine exploration and its environmental impact assessment: insights from international standards - Ma, Letian; Li, Jiabiao; Feng, Xuwen; Hao, Tianyao; Nan, Fangzhou (Frontiers in Marine Science, 2024)
Rising demand for marine resources has led to a great interest in seabed exploration and mining, while deep-sea environments are faced with cumulative effects of many human activities. Currently, conducting an environmental impact assessment for deep-sea exploration and mining is challenging due to the dynamic nature and a lack of high-quality data. The International Seabed Authority (ISA), which charges with regulating human activities on the seabed beyond the continental shelf, requires contractors to establish both geological and environmental baselines. Also, the ISA provides a general environmental guideline for exploring various seabed resources. However, standardization of its implementation would need to be addressed with specified technical international standards. The marine technology subcommittee of International Standardization Organization (ISO) contributes to the study of standards on deep-sea geological, geophysical and biological surveys, also on marine environmental protection. In this review, we explore two broad aspects of ISO standards: (1) the development of marine geological and geophysical exploration standard, which may help to establish geological map in the seabed area. (2) the current state of development of a series of Marine Environmental Impact Assessment (MEIA) standards, which could standardize the environmental surveys and monitoring activities in the seabed area. We also consider the standardization gap between MEIA and seabed mining, and propose future focus on coordination relationship between marine exploration and environmental protection.